TEMPORAL VARIATION OF VEGETATION INDEX RELATED TO PRECIPITATION DYNAMICS IN FORESTED AREA OF BOJONEGORO REGENCY - Heri Mulyanti; Oktavianus Cahya Anggara; Bagus Saputra; Nabila Nalalizza; Eka Luluk Fitriani (Universitas Sebelas Maret (UNS), 2026)
Vegetation dynamics in monsoonal regions are related to climate variability, particularly precipitation. Changes in precipitation may be reflected in vegetation conditions, yet studies on the temporal relationship between NDVI and Rainfall at the regional scale remain limited. This study aims to analyze NDVI dynamics and their relationship with precipitation in Bojonegoro Regency, East Java, during 2001–2023. Using Landsat satellite imagery and CHIRPS precipitation data, the Normalized Difference Vegetation Index (NDVI) was analyzed to evaluate seasonal and interannual vegetation patterns. NDVI values were calculated for April–May and October, representing the end and beginning of the rainy season. Results show that NDVI tends to be higher at the end of the rainy season, with a median value of 0.365, compared to 0.254 at the beginning. The highest NDVI was recorded in 2021, with a median of 0.596. Forested areas demonstrated greater resilience to climate variability than croplands or degraded land. NDVI and Rainfall exhibited a complex relationship, with significant correlations observed only in 2001 at lags –2, –1, and +2. The lag time responses of NDVI after specified precipitation can be used for forest management and planting. The analysis suggests that detailed assessments using time series data are necessary for a clearer understanding. NDVI alone is insufficient, and field validation is required to confirm satellite-based interpretations. Therefore, planned management required to enhance ecosystem resilience to climate change.